Measurement of Reading Level Index in Salatiga City - Warsito, Budi; Hakim, Arief Rachman; Fatmawati, Endang (Department Library of Governance Institut of Home Affairs, 2023)
Abstract Background: Concerning the increase in reading interest in Salatiga City, a scientific study is needed, which can become the basis for a policy decision so that the index will increase. Purpose: To measure the level of interest in reading people in Salatiga in 2023 comprehensively and precisely. Method: Methods using quantitative. This research was conducted using sampling techniques and research instruments, which have been determined by the National Library of Indonesia and have become national standards. The location of the research was carried out in the city of Salatiga, and sampling was done by simple random technique. Respondents amounted to 399 people with criteria aged 10-69 years. Measurements were made using five key performance indicators, namely reading frequency per week, duration of reading per day, amount of reading material per quarter, frequency of internet access per week, and duration of internet access per day. Result: The study results show that the value of the reading enthusiasm of the people in Salatiga City in 2023 is in the High category (62.13). Conclusion: Measurement of reading level index in Salatiga City to improving community reading literacy. The index value for the level of fondness for reading from the results of the 2023 study has decreased from the 2022 measurement, which had an index of 64.08. Keywords: Reading Frequency; Reading Duration; Reading Preferences; Reading Activity; Literacy Culture